2013
DOI: 10.1137/120874059
|View full text |Cite
|
Sign up to set email alerts
|

Smoothness-Increasing Accuracy-Conserving Filters for Discontinuous Galerkin Solutions over Unstructured Triangular Meshes

Abstract: Abstract. The discontinuous Galerkin (DG) method has very quickly found utility in such diverse applications as computational solid mechanics, fluid mechanics, acoustics, and electromagnetics. The DG methodology merely requires weak constraints on the fluxes between elements. This feature provides a flexibility which is difficult to match with conventional continuous Galerkin methods. However, allowing discontinuity between element interfaces can in turn be problematic during simulation postprocessing, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…This is illustrated in Figure 5. In this figure, a kernel scaling of H = mh is used for the convolution kernel in the SIAC filter for a discontinuous Galerkin approximation over a uniform mesh designated by h. We can see that error reduction actually occurs even when H < h. Superconvergent order starts to occur around H = h and errors start to increase for H > h. The sweetspot of reduced errors and superconvergence seems to occur around H = h. Although the typical meshes tested involve some type of translation invariance, the SIAC filter has also been tested over unstructured triangular meshes with promising results [10,12]. For example Figure 6 shows the difference in the pointwise errors for the DG approximation versus the SIAC filtered DG approximation.…”
Section: Mesh Geometrymentioning
confidence: 88%
“…This is illustrated in Figure 5. In this figure, a kernel scaling of H = mh is used for the convolution kernel in the SIAC filter for a discontinuous Galerkin approximation over a uniform mesh designated by h. We can see that error reduction actually occurs even when H < h. Superconvergent order starts to occur around H = h and errors start to increase for H > h. The sweetspot of reduced errors and superconvergence seems to occur around H = h. Although the typical meshes tested involve some type of translation invariance, the SIAC filter has also been tested over unstructured triangular meshes with promising results [10,12]. For example Figure 6 shows the difference in the pointwise errors for the DG approximation versus the SIAC filtered DG approximation.…”
Section: Mesh Geometrymentioning
confidence: 88%
“…Although the characteristic length choice is obvious for uniform meshes (H = mesh size), there has been ongoing work on finding the optimal value for non-uniform and unstructured meshes [4,17,26]. In addition, introducing a rotation in the kernel leads to the problem of determining the optimal orientation.…”
Section: The Line Siac (Lsiac) Family Of Filtersmentioning
confidence: 99%
“…Regarding the kernel characteristic length, [14,17] used the formula H = m · h, with h being the largest element size, and performed global error analyses on known analytic fields for different values of m. They showed that asymptotically, the value m = 1 lead to optimal results. We performed a similar experiment and in Figure 11 we show the same filtered vortex after applying different characteristic lengths where one can appreciate that the value H = 0.675 (m = 1) gives the most satisfactory results.…”
Section: Lsiac Validation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A SIAC filter has the ability to extract a superconvergent solution from a DG approximation for different element types including quadrilateral, structured triangular, tetrahedral and even unstructured triangular meshes [17,21,18]. One-sided SIAC kernels have been proposed as an extension of this convolution-based postprocessing for simulations involving boundaries or sharp discontinuities such as shocks [24,35,26].…”
Section: Introductionmentioning
confidence: 99%